Makna Tari Inai Dalam Prosesi Malam Berinai Pada Adat Perkawinan Masyarakat Desa Teluk Majelis Kecamatan Kuala Jambi - Nurul Annisa Syafwan; Indrayuda Indrayuda (SENDRATASIK UNP, 2022)
This research is viewed from the meaning of dance about Tari Inai in the Malam berinai procession at the marriage custom of the Teluk Majelis village community, Kuala Jambi district. This type of research is qualitative and uses descriptive methods. The research instrument is the researcher himself and is assisted by supporting tools such as stationery and camera. By using literature study, observation, interviews and documentation is expected to collect the required information. Technique Source triangulation technique is a technique used to ensure the validity of this data. To analyze the data requires steps such as data collection, data presentation and drawing conclusions. The results showed that the Tari Inai is one of the traditional wedding ceremony processions of the East Malay ethnic group in Tanjung Jabung Timur. The meaning of the Tari Inai is as a night of giving blessings to the bride and groom who will lead a new life, as a night for a large family gathering, as a night to introduce the groom to the entire big family of the bride, and as a night of expressing welcome to the groom. who has entered the ranks of the bride's extended family. Tari Inai is also interpreted as a symbol of the willingness of both parents and family members to let go of the bachelors of their sons and daughters.